2021
DOI: 10.3390/ani11051397
|View full text |Cite
|
Sign up to set email alerts
|

Automated Operant Conditioning Devices for Fish. Do They Work?

Abstract: The growing use of teleosts in comparative cognition and in neurobiological research has prompted many researchers to develop automated conditioning devices for fish. These techniques can make research less expensive and fully comparable with research on warm-blooded species, in which automated devices have been used for more than a century. Tested with a recently developed automated device, guppies (Poecilia reticulata) easily performed 80 reinforced trials per session, exceeding 80% accuracy in color or shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 98 publications
(189 reference statements)
1
25
0
Order By: Relevance
“…Each subject was individually maintained for the duration of the experiment in a glass tank (22 × 50 × 32 cm) filled with 28 L of water (see Gatto et al 2021;Santacà et al 2021 for more details). Two trapezoidal structures (10 × 6 × 32 cm) made with transparent acetate sheets subdivided the tank in an hourglass-shaped testing compartment and two small lateral compartments (Fig.…”
Section: Apparatusmentioning
confidence: 99%
See 4 more Smart Citations
“…Each subject was individually maintained for the duration of the experiment in a glass tank (22 × 50 × 32 cm) filled with 28 L of water (see Gatto et al 2021;Santacà et al 2021 for more details). Two trapezoidal structures (10 × 6 × 32 cm) made with transparent acetate sheets subdivided the tank in an hourglass-shaped testing compartment and two small lateral compartments (Fig.…”
Section: Apparatusmentioning
confidence: 99%
“…In two separate studies, it was found that guppies discriminate numbers that differ by 1 unit up to 4 versus 5 items, corresponding to a 0.80 numerosity ratio (Bisazza et al 2014;Gatto et al 2021). As humans and some other mammals and birds (Mix et al 2002;Rugani et al 2013;Tomonaga 2008), guppies can integrate numerical and nonnumerical information to obtain a more accurate estimate but, if prevented from accessing the latter, they can discriminate based on the sole numerical information (Gatto et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations